Discipline-Based Servant Leadership Model for Effective School Principal Leadership: Conceptual Framework Development and Empirical Validation - Safwandi, Safwandi; Komariah, Aan; Suryana, Asep; Prihatin, Eka (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Despite extensive research on servant leadership and positive discipline, no existing framework integrates both into a coherent model for elementary educational leadership, particularly in collectivist cultural contexts. This study develops and empirically validates a discipline-based servant leadership framework for elementary school principals. Using a qualitative approach with systematic narrative review of literature from Scopus and Web of Science (2021–2024), followed by an instrumental single case study at an Indonesian elementary school involving 15 informants (principals, teachers, staff, and students), analysis was conducted through framework analysis using ATLAS.ti for network visualization. The framework consists of five integrated dimensions: transformative service, constructive discipline, structured empowerment, moral accountability, and continuous development. The central theoretical contribution is the conceptualization of “structured compassion” as an integrative principle resolving the dichotomy between service orientation and organizational accountability through the integration of Self-Determination Theory, Compassionate Leadership Theory, and Paradoxical Leadership Theory. Empirical validation identified 72 unique codes confirming framework implementability, while network analysis revealed strong cross-dimensional interconnections. The framework advances the literature by reconciling Indonesian cultural values of gotong royong and kerukunan with contemporary educational accountability requirements, offering a transferable model for collectivist educational contexts globally.